Tumorigenic effects of human mesenchymal stromal cells and fibroblasts on bladder cancer cells - Frerichs, Lucie M.; Frerichs, Bastian; Petzsch, Patrick; Köhrer, Karl; Windolf, Joachim; Bittersohl, Bernd; Hoffmann, Michèle J.; Grotheer, Vera (Frontiers in Oncology, 2023)
Background: Patients with muscle-invasive bladder cancer face poor prognosis due to rapid disease progression and chemoresistance. Thus, there is urgent need for new therapeutic treatment. The tumor microenvironment (TME) has crucial roles in tumor development, growth, progression, and therapy resistance. TME cells may also survive standard treatment of care and fire up disease recurrence. However, whether specific TME components have tumor promoting or inhibitory properties depends on cell type and cancer entity. Thus, deeper understanding of interaction mechanisms between the TME and cancer cells is needed to develop new cancer treatment approaches overcoming therapy resistance. Little is known about function and interaction between mesenchymal stromal cells (MSC) or fibroblasts (FB) as TME components and bladder cancer cells. Methods: We investigated functional impact of conditioned media (CM) from primary cultures of different donors of MSC or FB on urothelial carcinoma cell lines (UCC) representing advanced disease stages, namely BFTC-905, VMCUB-1 and UMUC-3. Underlying mechanisms were identified by RNA sequencing and protein analyses of cancer cells and of conditioned media by oncoarrays.Results: Both FB-and MSC-CM had tumor promoting effects on UCC. In some experiments the impact of MSC-CM was more pronounced. CM augmented the aggressive phenotype of UCC, particularly of those with epithelial phenotype. Proliferation, migratory and invasive capacity were significantly This is a provisional file, not the final typeset article increased; cisplatin sensitivity was reduced. RNA sequencing identified underlying mechanisms and molecules contributing to observed phenotype changes. NRF2 and NF-κB signaling was affected contributing to improved cisplatin detoxification. Likewise, Interferon Type I signaling was downregulated and regulators of epithelial mesenchymal transition (EMT) were increased. Altered protein abundance of CXCR4, hyaluronan receptor CD44, or TGFβ-signaling was induced by CM in cancer cells and may contribute to phenotypical changes. CM contained high levels of CCL2/MCP-1, MMPs and Interleukins which are well known for their impact on other cancer entities.Conclusions: CM of two different TME components had overlapping tumor promoting effects and increased chemoresistance. We identified underlying mechanisms and molecules contributing to aggressiveness of bladder cancer cells. These need to be further investigated for targeting the TME to improve cancer therapy.